Use and Application of Federal Advisory Committee Act (FACA) Database - Nicholls, Natsuko; Owen-Smith, Jason (International Journal of Population Data Science, 2018)
University experts can offer uniquely valuable insights for informing policy based on expertise they develop through research. The application of knowledge through public service is an important and understudied mechanism for translating academic expertise to government and other communities. Today universities encourage researchers to engage in public service, and often they actively provide institutional support to create a culture and environment where such pro bono work is regarded as an important activity by the research community. Yet the question remains as to whether or not a systematic mechanism exists to track, record, and measure the value of university expertise influencing policy within the context of research. We explore a useful but underutilized administrative data source, the Federal Advisory Committee Act (FACA) database, with an eye towards linking the federal service data to other sources in order to measure research impact in a sociopolitical setting. This publicly available dataset contains rich information on federal advisory committees that play an important role in shaping national programs and policies. Each year an average of 900 advisory committees with more than 60,000 members have provided either policy or grant review advice in 40 different issue areas. Our exploratory findings suggest a steady increase of academics in federal service, the different level of federal service contribution by universities, and the association between federal service and university R&D spending. We also discuss the importance of data cleaning when using administrative data for research and data linkage methods when linking federal service data to university research spending records.